Clinical value of 18F-FDG PET/CT in the management of HIV-associated lymphoma - Liu, Qi; Yang, Tao; Chen, Xiaoliang; Liu, Yao (Frontiers in Oncology, 2023)
HIV is still a major public health problem. At present, HIV-associated lymphoma remains the leading cause of deaths among people living with HIV, which should be paid more attention to. 18F-fluorodeoxglucose (FDG) PET/CT has been recommended in the initial staging, restaging, response assessment and prognostic prediction of lymphomas in general population. HIV-associated lymphoma is, however, a different entity from lymphoma in HIV-negative with a poorer prognosis. The ability to accurately risk-stratify HIV-infected patients with lymphoma will help guide treatment strategy and improve the prognosis. In the review, the current clinical applications of 18F-FDG PET/CT in HIV-associated lymphoma will be discussed, such as diagnosis, initial staging, response evaluation, prognostic prediction, PET-guided radiotherapy decision, and surveillance for recurrence. Moreover, future perspectives will also be presented.